EFFECTIVENESS OF TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS), BALANCE EXERCISES, AND QUADRICEPS SETINGG IN THE CASE OF BALANCE DISORDERS IN KNEE OSTEOARTHRITIS PATIENTS: A CASE REPORT - Putri, Elma Prida Hapsari; Sudaryanto, Wahyu Tri; Fitriananda, Eva (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Osteoarthritis is the most common degenerative disease that causes disability in the elderly. Defined as progressive articular cartilage wear and tear. The goal of this study was to see how well Transcutaneous Electrical Nerve Stimulation (TENS), Balance Exercise, and Quadriceps Setting worked in cases of Balance Disorders in Osteoarthritis Knee Patients. Case Presentation: A retired teacher, 68 years old. The patient complains of pain in her right knee, which happens when she first wakes up in the morning and when he walks lengthy distances. Management and Outcome: Patients receive therapy twice a week, with each session lasting 60 minutes. Transcutaneous Electrical Nerve Stimulation (TENS) and exercises were used to treat the patient. The Numeric Rating Scale (NRS) and the Berg Balance Scale (BBS) were used to assess pain. Discussion: Tenderness and motion discomfort decreased by one point after therapy, and balance improved by one point as measured by BBS, with a pre-therapy value of 14 and a post-therapy value of 23. Conclusion: In Osteoarthritis Knee patients, therapy in the form of Transcutaneous Electrical Nerve Stimulation (TENS) modalities and exercises is beneficial in lowering pain and improving balance values.